Objective: Use factoring to solve quadratic equations. Standard(s) being met: 2.8 Algebra and Functions.

Slides:



Advertisements
Similar presentations
Solving Quadratic Equations Using the Zero Product Property
Advertisements

8-2: Solving Systems of Equations using Substitution
Solve a System Algebraically
Table of Contents First, find the least common denominator (LCD) of all fractions present. Linear Equations With Fractions: Solving algebraically Example:
Solving Equations In Quadratic Form There are several methods one can use to solve a quadratic equation. Sometimes we are called upon to solve an equation.
Algebra 1: Solving Equations with variables on BOTH sides.
3.5 – Solving Systems of Equations in Three Variables.
Notes - Solving Quadratic Equations in Factored Form If ab = 0, then a = 0 or b = 0 If the product of two factors is zero, then at least one of the factors.
Equations Reducible to Quadratic
Solving a System of Equations by SUBSTITUTION. GOAL: I want to find what x equals, and what y equals. Using substitution, I can say that x = __ and y.
Solving Quadratic Equations by Factoring January 6, 2015 Pages
Example: 3x 2 + 9x + 6. Solving Quadratic Equations.
§ 3.6 Solving Quadratic Equations by Factoring. Martin-Gay, Developmental Mathematics 2 Zero Factor Theorem Quadratic Equations Can be written in the.
Factoring to Solve Quadratic Equations
5-5 Solving Quadratic Equations Objectives:  Solve quadratic equations.
Holt McDougal Algebra 2 Solving Rational Equations and Inequalities Solving Rational Equations and Inequalities Holt Algebra 2Holt McDougal Algebra 2.
Do Now 1) Factor. 3a2 – 26a + 35.
Example 1A Solve the equation. Check your answer. (x – 7)(x + 2) = 0
SOLVING QUADRATIC EQUATIONS Factoring Method. Warm Up Factor the following. 1. x 2 – 4x – x 2 + 2x – x 2 -28x + 48.
Elimination Method: Solve the linear system. -8x + 3y=12 8x - 9y=12.
EXAMPLE 1 Solve by equating exponents Rewrite 4 and as powers with base Solve 4 = x 1 2 x – 3 (2 ) = (2 ) 2 x – 3x – 1– 1 2 = 2 2 x– x + 3 2x =
2.1 – Linear and Quadratic Equations Linear Equations.
SECONDARY ONE 6.1a Using Substitution to Solve a System.
Solving Quadratic Equations Using the Zero Product Property March 18, 2014.
Solving Systems of Equations
Solving a System of Equations in Two Variables By Substitution Chapter 8.2.
Math I UNIT QUESTION: What do solutions of equations represent? Standard: MM1A3 Today’s Question: How do we solve quadratic equations algebraically?
Ch. 6.4 Solving Polynomial Equations. Sum and Difference of Cubes.
x + 5 = 105x = 10  x = (  x ) 2 = ( 5 ) 2 x = 5 x = 2 x = 25 (5) + 5 = 105(2) = 10  25 = 5 10 = = 10 5 = 5.
Topic 6.5. Solve Systems by Substitution Objectives: Solve Systems of Equations using Substitution Standards: Functions, Algebra, Patterns. Connections.
Warm-up. Systems of Equations: Substitution Solving by Substitution 1)Solve one of the equations for a variable. 2)Substitute the expression from step.
Solving Quadratic Equations. Find the quadratic equation if the solutions are 3 and -2. x = 3 x = -2 Make them equal zero. x – 3 = 0x + 2 = 0 (x – 3)(x.
Solving Quadratics Review. We must solve to get x 2 by itself 1 st !
3.2 Solve Linear Systems Algebraically Algebra II.
Solving Systems by Substitution (isolated) Solving Systems by Substitution (not isolated)
Elimination Method - Systems. Elimination Method  With the elimination method, you create like terms that add to zero.
Entry Task   by.
Equations Quadratic in form factorable equations
1-5 Equations Goals: Solve equations with one variable
Equations with Algebraic Fractions
3-2: Solving Systems of Equations using Substitution
Solving Systems of Equations
Warm-Up Solve the system by substitution..
A quadratic equation is written in the Standard Form,
Solving Equations by Factoring and Problem Solving
Solve a system of linear equation in two variables
Solving Quadratic Equations by Factoring March 16, 2015
3-2: Solving Systems of Equations using Substitution
Solving Systems of Equations using Substitution
3-2: Solving Systems of Equations using Substitution
Notes - Solving Quadratic Equations in Factored Form
3.2a – Solving Systems algebraically
Solving Quadratic Equations by Factoring
Algebra 1 Section 13.6.
10.4 Solving Quadratic Equations in Factored Form
You can find the roots of some quadratic equations by factoring and applying the Zero Product Property. Functions have zeros or x-intercepts. Equations.
Notes Solving a System by Elimination
If you can easily isolate one of the variables,
Warm-Up Solve the system by graphing..
3-2: Solving Systems of Equations using Substitution
Solve the linear system.
Equations Quadratic in form factorable equations
Chapter 8 Systems of Equations
3-2: Solving Systems of Equations using Substitution
3-2: Solving Systems of Equations using Substitution
9-5 Factoring to Solve Quadratic Equations
3-2: Solving Systems of Equations using Substitution
3-2: Solving Systems of Equations using Substitution
Solving Quadratic Equations by Factoring March 11, 2016
Solving Linear Systems by Graphing
Presentation transcript:

Objective: Use factoring to solve quadratic equations. Standard(s) being met: 2.8 Algebra and Functions

Steps for solving a quadratic equation: 3x 2 - 3x = 18 1.) Set the equation equal to zero. 3x 2 – 3x – 18 = 0 2.) Completely factor the quadratic expression. 3(x 2 – x – 6) = 0 3(x – 3)(x + 2) = 0 3.) Set any factor that contains a variable equal to zero and solve for the variable. x – 3 = 0 x = 3 x + 2 = 0 x = -2

4.) Check your solutions by substituting each of them for the variable in the original equation. 3x 2 – 3x = 18 3(3 2 ) – 3(3) = 18 3 · 9 – 9 = – 9 =18 18 = 18 3(-2) 2 – 3(-2) = 18 3 · 4 – (-6) = = = 18, So the solutions to 3x 2 -3x = 18 are 3 and -2.

Ex. 1, Solve each quadratic equation. a.) 15x 2 – 93x = x 2 – 93x + 18 = 0 3(5x 2 – 31 x + 6) = 0 3(x – 6)(5x -1) = 0 x – 6 = 0, x = 6 5x – 1 = 0 5x = 1 x = 1/5 x = 6, 1/5

Ex. 1, Solve each quadratic equation.  a.) 15x 2 – 93x = -18  b.) 128x 3 = 98x  c.) 6x 2 – 4 = 5x  d.) 12x 2 – 8x – 13 = 2  e.) 2x 2 + 3x - 20 = 7 – 2x 2

b.) 128x 3 = 98x 128x x = 0 2x(64x 2 – 49) = 0 2x(8x + 7)(8x – 7) = 0 2x = 0 x =0 8x + 7 = 0 x = -7/8 8x – 7 = 0 x = 7/8 x = 0, -7/8, 7/8

c.) 6x 2 – 4 = 5x 6x 2 – 5x – 4 = 0 (2x + 1)(3x – 4) = 0 2x + 1 = 0 2x = -1 x = -1/2 3x – 4 = 0 3x = 4 x = 4/3 x = -1/2, 1 1/3

d.) 12x 2 – 8x – 13 = 2 12x 2 – 8x -15 = 0 (6x + 5)(2x – 3) = 0 6x + 5 = 0 6x = -5, x = -5/6 2x – 3 = 0 2x = 3, x = 3/2 x = -5/6, 1 ½ x = -5/6, 1 ½ e.) 2x 2 + 3x - 20 = 7 – 2x 2 4x 2 + 3x – 27 = 0 (4x - 9)(x + 3) = 0 4x – 9 = 0 4x = 9, x = 9/4 x + 3 = 0 x = -3 x = 2 ¼, -3

Do page 146 together. Do page 145 on your own.